GAME SEBAGAI MEDIA PEMBELAJARAN KREATIF DAN MENARIK UNTUK MENINGKATKAN MINAT /MOTIVASI BELAJAR BAHASA INGGRIS PADA ANAK SEKOLAH DASAR - Yufenti Oktafiah; Dwita Laksita R (Bajang Institute, 2023)
English is the language of all countries in the world in its position as a global lingua franca. Indonesia must also place English in the same position so that it can compete more in international competition. English education in Indonesia has been carried out since elementary school. The objectives of learning English through game media include: increasing students' enthusiasm in learning English, improving students' basic English skills through fast learning because it is packaged effectively, creatively, and fun. Educational games can be interactive English learning media, making the learning process more fun and effective. Games are an alternative way that can be used to see some of the positive aspects that will be obtained from the elements of game activities. Educational games or games can be very effective in helping convey material and increasing student motivation to study harder